FILSAFAT, KETERBUKAAN DAN DIALOG: KEKRISTENAN DI JEPANG PASCA PERANG DUNIA II - Munte, Alfonso (Jurnal Lektur Keagamaan, 2024)
The aftermath of World War II significantly impacted dialogue and understanding between cultures, educational perspectives, and religions in Japan. This period saw widespread destruction and psychological trauma, leading to a sense of powerlessness and discouraging Western settlement. This paper aims to reintroduce Plato's philosophy within the context of Japan's post-war dialogue (Risō/理想), highlighting the country's philosophical contributions and its openness to religious institutions, including the participation of Christian congregations in government. Using a qualitative literature review of primary and secondary sources, this study finds that philosophical dialogue has positively influenced both the government and the populace. The intersection of various religions and Christianity in post-war Japan facilitated the survival and growth of Christianity, demonstrated by the enduring presence of the Way of the Cross and the pervasive influence of Christian values in Japan's religious, political, and cultural spheres.